2017
DOI: 10.1111/jphd.12205
|View full text |Cite
|
Sign up to set email alerts
|

Comparing self‐reported and clinically diagnosed unmet dental treatment needs using a nationally representative survey

Abstract: Our findings suggest that in general, self-reports are poor estimates for normative dental treatment needs but do have some merit in confirming non-needs. Exceptionally, self-reports do have suitable diagnostic accuracy for predicting orthodontic and endodontic needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 19 publications
0
25
0
Order By: Relevance
“…Additional information on the quality of the self-report were obtained by calculating the positive likelihood ratio (+LR) and negative likelihood ratio (-LR), where values ≥ 10 and ≤ 0.10 were respectively considered as strong evidence that self-report is a good indicator of the clinical oral condition 21 . Finally, the agreement level between the Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…Additional information on the quality of the self-report were obtained by calculating the positive likelihood ratio (+LR) and negative likelihood ratio (-LR), where values ≥ 10 and ≤ 0.10 were respectively considered as strong evidence that self-report is a good indicator of the clinical oral condition 21 . Finally, the agreement level between the Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…Although self-reported oral health is an acceptable proxy for periodontal disease at the population level and for epidemiological surveys, it may not be of adequate agreement to clinical measures of disease (39). Previous studies have shown that self-reported oral health information is highly specific but not as sensitive (41). In the case of periodontal disease, individuals were able to report that they do not have periodontal disease nor did they need dental treatment, with greater accuracy than those who did in fact have the condition or unmet treatment needs (41).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that self-reported oral health information is highly specific but not as sensitive (41). In the case of periodontal disease, individuals were able to report that they do not have periodontal disease nor did they need dental treatment, with greater accuracy than those who did in fact have the condition or unmet treatment needs (41). Although clinical measures of periodontal disease, such as gingival probing depths, would provide power to our study, such measures have not been linked to electronic medical records in Canada.…”
Section: Discussionmentioning
confidence: 99%
“…Although self-reported oral health is an acceptable proxy for periodontal disease at the population level and for epidemiological surveys, it may not adequately measure the clinical manifestations of disease [41]. Previous studies have shown that self-reported oral health information is highly specific but not sensitive [43]. In the case of periodontal disease, individuals were able to report that they did not have periodontal disease nor did they need dental treatment with greater accuracy than those who did in fact have the condition or unmet treatment needs [43].…”
Section: Baseline Characteristics �mentioning
confidence: 99%